POLA PEMANFAATAN SUMBER DAYA, SUBSISTENSI DAN POLA HUBUNGAN PATRON-KLIEN MASYARAKAT NELAYAN DANAU TEMPE, SULAWESI SELATAN - Fatriyandi Nur Priyatna; Sumartono Sumartono (Jurnal Matematika Sains dan Teknologi, 2011)
The objective of this article is to study the relation among resource utilization pattern, subsistence and patron client relationship in Danau Tempes fisheries community, South Sulawesi, using a qualitative research method. Data were collected purposive for both small scale and relatively big scale fisheries by means of indepth interview and observation. Scotts moral economy framework was used to analyze the nature of social phenomena. The results show that fisheries resource scarcity due to intensive fishing activities were the reason behind fisheries communitys strategy to handle the subsistence crisis. Patron-client relation was used by fisheries community which hold trust and kinship in regard. The relation was also based on mutual solution in terms of social reciprocity. Clients tend to maintain their relation to patrons due to safety and security reasons from their subsistence crisis, eventhough they have smaller economic profit from that relation. While patrons help clients based on social obligation to help others.